L’écriture après l’écriture : Öyvind Fahlström, au prisme de la pensée de Vilém Flusser - Ludovic Bernhardt (Appareil)
The radical thought of Vilém Flusser regarding mutations of the alphabet linked to apparatuses, cannot escape from a perspective of art and poetry. From the 1950s to the mid 1970s, the Swedish artist and writer Öyvind Fahlström has undertaken to disturb linear codes of written language, with his manipulation processes of words, images and sounds. Through the encounter of Flusser and Fahlström’s fields of reflexion and creation, we would like to stress the question of apparatuses in a redefinition of writing, leading to a recoding of art : indeed, in the second half of twentieth century, alphabetic writing seems to be on the threshold of radical transformations. In this sense, it’s all about reformulation of writing and poetry and their possible emancipation from historical and linear confines. A cybernetic dimension is claimed by Flusser and is widely explored in some of Fahlström’s researches. In this way, Flusser develops a thought of Post-History which introduces the question of a new regime as well as a reshaping of poetical worlds ; according to Flusser, poetry has to be cybernetically interpreted in order to open new esthetical fields, while also considering that very high risks are involved in these codes transfers. Fundamentally, Flusser’s thought and Fahlström’s art announce the coming of a writing after writing that renews our relationship with images, texts and poetry.